THE EVOLUTION OF PEACEKEEPING: SUEZ, RWANDA AND DEMOCRATIC REPUBLIC OF THE CONGO - Leal, Maria Fernanda Affonso; Santin, Rafael; de Magalhães, David Almstadter (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
Since the first peacekeeping operation was created until today, the UN has been trying to adapt them to the different contexts in which they are deployed. This paper analy- ses the possibility of a bigger shift happening in the way the United Nations, through the Security Council, operates their Peacekeeping Operations. The change here ad- dressed includes, mainly, the constitution of more “robust” missions and the newly introduced Intervention Brigade in the Democratic Republic of Congo. By presenting three missions (UNEF I, UNAMIR and MONUSCO) deployed in different historic periods, we identified various elements in their mandates and in the way these were established which indicate a progressive transformation in the peacekeeping model since the Cold War - when conflicts were in their majority between States – until present days, when they occur mostly inside the States.